Tree biomass and of understorey and litter accumulated in Eucalyptus urophylla x Eucalyptus grandis - Salvador, Simone Martini; Schumacher, Mauro Valdir; Stahl, James; Santos, Joel Carvalho (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
This study aimed to quantify the biomass in different parts of the trees, the litter accumulated on the ground and in the understory, and was conducted with Eucalyptus urophylla x Eucalyptus grandis, at seven years of age, in two different soils of Telêmaco Borba city - PR. Soil A (Cambisol Tb dystrophic Latosolic), characterized in that sandy texture and soil B (Rhodic Haplortox) with clayey. Delimited to four plots located on each floor, making the measurement of all diameters and selection of trees to be felled. The trees were cut at soil level, and the fractionated components: leaves, twigs, bark, stem wood and roots, collecting a representative sample of each fraction as well as the weight thereof, to determine biomass. For the analysis of litter accumulated were collected 10 samples in each portion with an iron frame of 30 cm x 30 cm. All the vegetation contained within the footprint of each felled tree (7.5 m² ), it was regarded as understory all the biomass collected above and below ground. The woody biomass total Eucalyptus urophylla x Eucalyptus grandis to soil A and B was 257.99 and 301.20 Mg ha-1, respectively. The litter accumulated on the soil was higher in soil B, equivalent to 16.62% in relation to the ground A. Since the understory had total biomass of 1.08 Mg ha-1 for soil A, which is 47.22% above the ground B. It was concluded that the total tree biomass soil B than total tree biomass soil A, but the components of woody biomass and litter accumulated in soil, showed a reduction when compared with the soil components B, except the root component and understory, which showed higher total biomass in the soil A.